CORRELATION OF SOCIAL WELFARE WITH THE DEVELOPMENT OF JAPANESE POPULAR CULTURE AFTER WORLD WAR II - AULIAWAN, ALTHAF GAUHAR; SANTOSO, TEGUH (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2023)
Social welfare is a condition that humans strive to achieve a decent life in terms of material, social and spiritual aspects. After World War II, Japan was known as a country that experienced rapid economic and social welfare improvements. In addition, a wide range of Japanese popular culture products such as Manga & Anime, J-Pop, Video Games, and others have also grown and accompanied the established life of Japanese society. Therefore, Japanese popular culture has been supported and can spread to all corners of the world. This situation can indirectly improve the economy and existence of the Japanese state internationally, although, since the 1990s, Japan has experienced a lost decade. This study aims to discover in depth the correlation between the welfare of Japanese society and the development of Japanese popular culture after World War II. This study uses historical and descriptive qualitative methods with a multidisciplinary approach, such as history, social science, and culture. The results of this study show that social welfare is not a factor that can directly relate to or influence the development of Japanese popular culture. Other factors that lead to a marketing strategy and technology utilization, such as talented creators who have been good at finding opportunities, mass media culture, and Japanese government policies can influence the development of Japanese popular culture in domestic and abroad.